Impact of job rotation system on the employees performance - Based on Chinese state-owned enterprises - Guanxiong Liang; Debbra Toria Nipo; Sing Yun Wong (Human Resource Management Academic Research Society (HRMARS), 2023)
Human capital is always considered as the most valuable asset of an organization, which affects the overall profitability of companies. However, some studies have found the problems caused by unmatched skills and specific job vacancies, highlighting the significance of job rotation system. This study aims to explore the impact of job rotation system on the performance of employees from Chinese state-owned enterprises (via training, commitment, development chances), utilising human capital theory and ability, motivation, opportunity theory. This study also seeks to investigate the moderators of aforementioned relationship. This study employed a synthesized literature review to investigate the relationship between job rotation and employee performance based on a 10-year longitudinal and comprehensive analysis of prior studies. It is obvious that individual as well as organizational performance significantly change after rotation regardless of industries. Meanwhile, from numerous data collected previously, we find that gender has no significant influence from job rotation to employee performance, whereas age and tenure are playing important roles in moderating the relationship. With the findings summarized from this study, several practical recommendations are given accordingly to human resource departments in state-owned enterprises, scholars and researchers in relevant field.